A Practical Method For Calculating Cylindrical Shells - Davlyatov Sh.M; Egamberdiyev B.O (The American Journal of Engineering and Technology, 2020)
This article outlines the main provisions of the proposed method of determining the stress-strain state of cylindrical shells. The method can be used to calculate the various sheet structures, such as rectangular and cylindrical steel tanks for the storage of fluid substances.